(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
X-ray computed tomography (CT) is a relatively new technology which has been used as a powerful research tool mainly by vertebrate palaeontologists. CT allows scientists to visualise internal features of fossils and rocks non destructively, just as medical scanners di for the human body. High-resolution industrial scanners provide cross sections of fossils at a resolution of 20 microns or less. We present the application of CT to two paleobotanical specimens: a petrified trunk of a Cycadeoidea from the Late Jurassic of England and a silicified cone Araucaria mirabilis from the Jurassic Cerro Cuadraro Petrified Forest in Patagonia, Argentina. In the three longitudinal and four cross-sections of the Cycadeoidea trunk, a multitude of internal structures could be observed, including pith, xylem, cortex, vascular bundles, floral cones and leaf bases. In central longitudinal and median transverse sections, the perfectly preserved cone Araucaria mirabilis pith, xylem, vascular bundles, seeds and ovuliferous scales are clearly visible. In order to test the resolution of the CT a second, less complete, but similarly well preserved specimen of A. mirabilis has been cut and sliced for a thin section.